Responsiveness Of Public Complaints On The Integrated Road And Bridge Reporting Information System Application (SILAT JANTAN) In Madiun District - Yuyun Gita Mustifa; Sri Roekminiati; Ika Devy Pramudiana; Aris Sunarya (Prodi Sosiologi Agama, 2024)
Public services are the standard for government effectiveness in encouraging the realization of a good government system. In Madiun Regency the problem is the same as in other cities or districts in Indonesia, namely road damage. The people of Madiun Regency want all complaints to be responded to by Madiun Regency PUPR Service officials. This research uses a qualitative descriptive method or approach. Research data was obtained through observation of the use of the SILAT JANTAN application, interviews with Madiun Regency PUPR Service employees and the community, as well as documentation. This responsiveness analysis uses five elements of responsiveness, namely complaints from the public in 2023, the response of officials in responding to complaints, the use of complaints as reference material for service improvement, the actions of organizational officials in providing service satisfaction and the placement of the public by officials in the applicable service system. The research results show that the authorities in responding to complaints do not delay and are communicative in responding to complaints and processing report data from the public through the SILAT JANTAN application and submitting road repair requests. There are still few people who make complaints through the SILAT JANTAN application because many people do not know about the application. Community involvement is really needed because information from the community is useful for policy planning. For example, when people complain about damaged roads but don't know where to report it, the Madiun Regency PUPR Service launches an innovative reporting application system related to damaged roads. In providing satisfaction to the community, the PUPR Department is trying to be more targeted in handling road damage. The community is satisfied with the authorities' quick response in carrying out road repairs which are often complained about because it can prevent bad things from happening. The provision of services at the Madiun Regency PUPR Service does not involve discrimination, tries to be fast, professional and in accordance with established service standards. From the results of this research, so that community involvement meets expectations, Madiun Regency PUPR Service officials can increase socialization regarding the SILAT JANTAN application so that the application is known to many people.